2013
DOI: 10.1371/journal.pone.0055897
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Down of PRAME Increases Retinoic Acid Signaling and Cytotoxic Drug Sensitivity of Hodgkin Lymphoma Cells

Abstract: The prognosis for patients with Hodgkin lymphoma (HL) has improved in recent decades. On the other hand, not all patients can be cured with the currently established therapy regimes and this therapy is associated with several adverse late effects. Therefore it is necessary to develop new therapy strategies. After treatment of L-540 HL cells with 5′-azacytidine (5AC), we observed increased expression of the preferentially expressed antigen in melanoma (PRAME). In addition, we detected an increased resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…For instance, different expression levels of preferentially antigen expressed in melanoma (PRAME), a repressor of retinoic acid signaling, seem to affect ATRA sensitivity in cHL cell lines. 38 Our own findings obtained after derepressing treatment with the DNA-demethylating agent 5-Aza and the histone deacetylase inhibitor TSA support the idea that a master repressor of the B-cell program is selectively active in Hodgkin lymphoma, but epigenetically silenced in B-NHL and normal B cells. We may also have uncovered a putative role of the B-cell phenotype as a tumorsuppressive principle and novel vulnerability of cHL cells: different agents that led to the reexpression of B-cell-specific genes despite their pharmacologically distinct modes of action turned out to be toxic for cHL cells.…”
Section: Discussionsupporting
confidence: 59%
“…For instance, different expression levels of preferentially antigen expressed in melanoma (PRAME), a repressor of retinoic acid signaling, seem to affect ATRA sensitivity in cHL cell lines. 38 Our own findings obtained after derepressing treatment with the DNA-demethylating agent 5-Aza and the histone deacetylase inhibitor TSA support the idea that a master repressor of the B-cell program is selectively active in Hodgkin lymphoma, but epigenetically silenced in B-NHL and normal B cells. We may also have uncovered a putative role of the B-cell phenotype as a tumorsuppressive principle and novel vulnerability of cHL cells: different agents that led to the reexpression of B-cell-specific genes despite their pharmacologically distinct modes of action turned out to be toxic for cHL cells.…”
Section: Discussionsupporting
confidence: 59%
“…Expression of PRAME serves as a poor prognostic marker in many cancers [18][19][20][21] . Consequently, the knockdown of PRAME is expected to be an interesting option for the development of new therapeutic strategies for cancer [22] . Since the clinical significance of PRAME expression in HCC is totally unknown, the aim of the current study was to clarify the significance of PRAME in HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, among the top genes highly expressed in SKOV-3 cells there is PRAME that in a wide variety of human malignancies correlates with poor clinical outcome [83]. It has been reported that PRAME proteins are associated to self-renewal cell maintenance [84] and are currently considered as potential target to hamper cancer cell proliferation [85]. …”
Section: Discussionmentioning
confidence: 99%